Family‐focused recovery: Perspectives from individuals with a mental illness. (24th August 2018) - Waller, Susan; Reupert, Andrea; Ward, Bernadette; McCormick, Francis; Kidd, Susan
Abstract: Family members often provide significant support and care to their relative who has a mental illness. Nonetheless, how family members might be part of an individual's mental health recovery journey is rarely considered. The aim of this study was to investigate how those with a mental illness define 'family' and the role of family (if any) in their recovery journey. A qualitative approach was used. Purposive sampling and snowballing were used to recruit and conduct semi‐structured interviews with 12 people who have been diagnosed with a severe mental illness. Participants defined family in various ways with some being very inclusive and others more selective. There was acknowledgement that family contributed to the individual's recovery in a myriad of ways, although the need for boundaries was stressed. While no participants suggested that their family might become active treatment facilitators, they did want clinicians to support them in talking to their family about their mental illness. A multifaceted approach is needed to promote family‐focused recovery practice. The needs of different family members and the needs of the family as a group should be considered concurrently alongside the individual's needs in their recovery plan. Individual and relational components of recovery should be embedded in policy and clinical practice.